2022
DOI: 10.3389/fmicb.2022.913700
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approaches Revealed the Associations of Host Metabolism and Gut Microbiome With Phylogeny and Environmental Adaptation in Mountain Dragons

Abstract: The molecular basis enabling the adaptation of animals to spatially heterogeneous environments is a critical clue for understanding the variation, formation, and maintenance of biodiversity in the context of global climate change. Mountain dragons (Agamidae: Diploderma) thrive in the Hengduan Mountain Region, a biodiversity hotspot and a typical spatially heterogeneous environment. Here, we compare the liver and muscle metabolome and gut microbiome of 11 geographical populations from three Diploderma species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…This aligns with our earlier investigations conducted on laboratory-acclimated lizards collected from various geographic sites. 64 , 65 Kueneman et al. 30 reported that amphibian skin alpha-diversity was consistently correlated with temperature-associated climatic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with our earlier investigations conducted on laboratory-acclimated lizards collected from various geographic sites. 64 , 65 Kueneman et al. 30 reported that amphibian skin alpha-diversity was consistently correlated with temperature-associated climatic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences with an exact match or 100% sequence similarity were selected as the final amplicon sequence variants (ASVs) and a table of characteristics was produced. Subsequently, the classify-sklearn module within the QIIME2 software (Version 2020.6.0, https://qiime2.org/ ) (Zhu et al 2022 ) package was used to compare the collected ASVs with the Silva database ( http://www.arb-silva.de/ ) (Quast et al 2013 ) using a confidence level of 99% to determine the taxonomy of each ASV.…”
Section: Methodsmentioning
confidence: 99%